Preparation, Characterization, and Anti-Lung Cancer Activity of Tetrandrine-Loaded Stealth Liposomes - Fang Z; Lin P; Gao R; Yang W; Zhou A; Yu W (International Journal of Nanomedicine, 2024)
Zhengyu Fang,1,* Peihong Lin,1,* Rui Gao,1,* Wenjing Yang,1 Aizhen Zhou,2 Wenying Yu1,3 1School of Pharmacy, Hangzhou Medical College, Hangzhou, 310013, People’s Republic of China; 2Department of Traditional Chinese Medicine, Zhejiang Pharmaceutical University, Ningbo, 315500, People’s Republic of China; 3Key Laboratory of Neuropsychiatric Drug Research of Zhejiang Province, Hangzhou Medical College, Hangzhou, 310013, People’s Republic of China*These authors contributed equally to this workCorrespondence: Aizhen Zhou; Wenying Yu, Tel +86 571 88215623, Email zhouaz@zjpc.net.cn; zjyuwenying@163.comBackground: Tetrandrine (Tet), a bisbenzylisoquinoline alkaloid, is a potential candidate for cancer chemotherapy. However, Tet has poor aqueous solubility and a short half-life, which limits its bioavailability and efficacy. Liposomes have been widely utilized to enhance the bioavailability and efficacy of drugs.Methods: In this study, Tet-loaded stealth liposomes (S-LPs@Tet) were prepared by ethanol injection method. Furthermore, physicochemical characterisation, biopharmaceutical behaviour, therapeutic efficacy, and biocompatibility of S-LPs@Tet were assessed.Results: The prepared S-LPs@Tet had an average particle size of 65.57 ± 1.60 nm, a surface charge of − 0.61 ± 0.10 mV, and an encapsulation efficiency of 87.20% ± 1.30%. The S-LPs@Tet released Tet in a sustained manner, and the results demonstrated that the formulation remained stable for one month. More importantly, S-LPs significantly enhanced the inhibitory ability of Tet on the proliferation and migration of lung cancer cells, and enabled Tet to escape phagocytosis by immune cells. Furthermore, in vivo studies confirmed the potential for long-circulation and potent tumor-suppressive effects of S-LPs@Tet. Moreover, ex vivo and in vivo safety experiments demonstrated that the carrier material S-LPs exhibited superior biocompatibility.Conclusion: Our research suggested that S-LPs@Tet has potential applications in lung cancer treatment.Keywords: tetrandrine, S-LPs, lung cancer, immune escape, in vivo imaging